Konseling Individu dengan Teknik Thought Stopping dalam Mengatasi Perilaku Agresif - Dwi Rahmawati; Suryati Suryati; Zhila Jannati (Journal of Society Counseling, 2023)
Aggressive behavior can cause conflicts, fights, acts of violence and also make relationships with other people worse. This study aims to determine the description of aggressive behavior on client N at the Ar Rahman Drug Rehabilitation Center. This research uses a qualitative approach and case study method. Data collection techniques in this study are observation, interviews and communication. Data analysis techniques in this study are pattern matching, explanation and time series analysis. The subjects of this study were client "N", client "N"'s friends and addiction counselor. The results of this study are: (a) an overview of the aggressive behavior experienced by client "N" seen from four aspects, namely the first on the physical aggression aspect in which Client N does not beat, push, kick, even pinch, the second on the verbal aggression in which client N rejects orders and advice given to him. Third, in the aspect of hostility, client N has a sense of injustice within him, and finally in the aspect of anger, where Client N easily gets annoyed with other people. (b) the implementation of individual counseling using the tough stopping technique was carried out in four meetings with three stages, namely the initial stage, the middle stage and the final stage, and (c) the description of aggressive behavior after the implementation of individual counseling using the tough stopping technique, namely the client's physical aggression aspect N can act more calmly, can maintain attitude in the surrounding environment. In the verbal aggression aspect, client N feels more relaxed in dealing with other people, begins to accept advice or invitations from someone. In the aspect of hostility, client N feels the pain has diminished and also focuses his mind on being calmer, able to think better, longer for the future and his future, trying to forgive. And lastly, the client N aspect begins to be able to control the frustration that occurs and is much calmer between his mind and heart.